Efecto de enmiendas y microorganismos en el rendimiento y producción en cultivo de maíz, en el cantón Bolívar - Solorzano Ganchozo, Kelvin Vicente (2025)
This research was carried out during the dry season at the facilities of the Escuela Superior Politécnica Agropecuaria de Manabí Manuel Félix López, in the parish of Calceta, Bolívar canton, with the objective of evaluating the effect of soil amendments and microorganisms on the growth, yield, and production of maize. The study was experimental in nature, with an explanatory scope and a quantitative approach. The research included six treatments, including the control, using amendments (Biochar) and plant growth-promoting microorganisms (Trichoderma and Bacillus sp.). The combined treatments of Biochar, Trichoderma, and Bacillus sp. showed a significant increase in plant height, number of leaves, stem diameter, and ear production. The most effective treatment was the one that integrated the three components, outperforming the control in several yield replicates. The findings highlight the relevance of soil amendments and microorganisms for sustainable agriculture. Trichoderma and Bacillus are identified as key plant growth promoters, enhancing plant health and nutrient assimilation. Biochar also contributes to soil fertility, suggesting a promising approach for agriculture in Manabí. The research confirms that the use of organic amendments and microorganisms can enhance maize yield in Bolívar canton, offering a viable alternative to improve agricultural sustainability and the socioeconomic well-being of farmers.